The Influence of Social Media and E-Commerce Based Affiliate Marketing on Customer Interest and Purchase Decisions: A Literature Review - Bramanto, R. Handi; Pramudani, Nadia; Fadhillah, Murni; Khaneisya, Rashell Puteri; Redjeki, Finny (Institute of Computer Science (IOCS), 2025)
Affiliate marketing has emerged as a prominent digital marketing strategy, especially through social media and e-commerce platforms, in the era of rapid technological globalization. This literature review aims to analyze the influence of social media and e-commerce-based affiliate marketing on customer interest and purchasing decisions. The study employed a purposive sampling technique and reviewed 10 selected sources, including peer-reviewed journals, theses, proceedings, and other academic literature published between 2018 and 2024. The inclusion criteria were based on relevance to the research topic and methodological quality. Findings from the reviewed literature consistently indicate that affiliate marketing via social media and e-commerce significantly enhances customer interest and drives purchasing decisions by leveraging personalized, visual, and trust-based communication. In conclusion, affiliate marketing strategies integrated with social media and e-commerce platforms are influential tools that shape consumer behavior and decision-making in the digital marketplace